Pengaruh Tingkat Kepatuhan Pelaporan SPT Tahunan Terhadap Penerimaan Pajak di Kantor Pelayanan Pajak Madya Dua Bandung - Rahmawati, Rina; Syahrinullah, Syahrinullah (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
This study aims to find out how the level of compliance with the reporting of the Annual Tax Return of Taxpayers affects tax revenue at the Intermediate Tax Service Office of Bandung. The variables used in this study are compliance with the reporting of the Annual Tax Return of Taxpayers and Tax Revenue. This research focuses on the data of taxpayers registered at the Intermediate Tax Service Office of Intermediate Dua Bandung. The method used in this study is a quantitative method using regression analysis with SPSS version 24. The data collection technique is through primary data and secondary data. Primary data is collected through the reporting of Taxpayer Annual Tax Returns and Tax Revenue Data at the Intermediate Tax Service Office in Bandung in the 2021-2023 period. Based on the research that has been conducted, it is concluded that compliance with the reporting of the Annual Tax Return of Taxpayers does not have a significant influence on tax revenue at KPP Madya Dua Bandung